Utilizing Indigenous Cultural Resources in Challenging Gender-Based Violence: A Case of the Zezuru of Zvimba, Zimbabwe - Chirongoma, Fungai (Religion compass, 2025)
Gender-based violence is a pervasive social issue in Africa. Some religious and cultural beliefs and practices inform gendered social norms that perpetuate and promote gender-based violence. African religion and culture encompass several harmful practices that expose women to gender-based violence. It is against this background that some studies propose the abolishment of some African religious and cultural practices that perpetuate violence against women. Other studies emphasize strengthening of the judiciary systems, while others suggest conducting gender-based violence campaigns, workshops and seminars as well as the establishment of shelters for abused women as strategies to address the scourge of gender-based violence. I propose utilizing African indigenous cultural resources or African indigenous knowledge such as proverbs, myths, idioms, cultural practices, and traditional stories to deconstruct oppressive gendered social norms and challenge gender-based violence. While African religion and culture have been critiqued for producing norms that promote gender-based violence, it is significant to note that religion and culture is not always bad news to women, there are resources within African religion and culture that are affirmative. I argue that employing indigenous knowledge or African philosophies to solve the problem of gender-based violence in the African context can be of significance in mitigating gender-based violence. I further argue that African indigenous cultural resources such as proverbs, idioms and taboos, unlike Domestic Violence Acts and policies which are sometimes misinterpreted and misunderstood, indigenous resources or knowledge can be easily embraced given that it is part of the everyday norms and values that influence the behaviour of the African people.